PENGARUH POLITICAL CONNECTION DAN FOREIGN OWNERSHIP TERHADAP NILAI PERUSAHAAN MELALUI CORPORATE SOCIAL RESPONSIBILITY - Tangke, Paulus (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to examine the effect of political connection and foreign ownership on firm valueÂ through corporate social responsibility by using secondary data in the form of financial statementsÂ of non-financial companies listed on the Indonesia Stock Exchange for the period 2006-2015. ThisÂ study uses path analysis with a multiple regression statistical test with the help of SPSS Version 24Â software. This study uses stakeholder theory as the main theory and legitimacy theory as a supportingÂ theory. The results of this study indicate that Political Connection has a positive and significant effectÂ on Corporate Social Responsibility but has no significant effect on Firm Value. While Foreign Ownership has a positive and significant effect on CSR and Corporate Value. The results of the sobelÂ test from this study indicate that CSR is a type no mediation in relation to political connection withÂ Corporate Value, also in the relationship of foreign ownership with Corporate Value, the CSRÂ variable is type no mediation.